Pathogenic Bacteria Detection: A Hierarchical 3D Nanostructured Microfluidic Device for Sensitive Detection of Pathogenic Bacteria (Small 35/2018). Issue 35 (29th August 2018) - Jalali, Mahsa; AbdelFatah, Tamer; Mahshid, Sahar Sadat; Labib, Mahmoud; Sudalaiyadum Perumal, Ayyappasamy; Mahshid, Sara
Abstract : In article number1801893, Sara Mahshid and co‐workers develop a nanostructured fluidic device for sensitive analysis of pathogenic bacteria based on a hierarchical nano/micro‐islands detection platform enabling direct, rapid, and quantifiable detection of bacteria. Performance of the integrated device in probe‐free optical detection of pathogenic bacteria such as Escherichia coli and optoimmunocapturing of antibiotic resistant bacteria such as methicillin‐resistant‐ Staphylococcus‐aureus shows promise in future point‐of‐care devices.